A violência contra as mulheres e a determinação do estatuto de refugiada - Leite, Ana Marta Xavier Ferreira (2018)
Violence against women and the determination of the refugee’s status is the title of the study developed for the Master Course in Law and Security, taught and attended at the Faculdade de Direito da Universidade Nova de Lisboa. As is understandable from the title, the study focuses on the interaction between the concepts of violence against women, i.e. gender violence, and the determination of the refugee’s status. The present dissertation aims to show that half of the world's refugee population today is composed of women and girls, and among refugees, women represent the most vulnerable group. During our work, we have been able to find stories and reports of crimes committed against women in their daily lives, in their homes, by their own family and by society. Some are able to flee and claim the right to asylum outside their country of origin, waiting for the granting of the refugee status. We will address situations of women who are forced to escape from their countries of origin because they are being victims of persecution, of sexual and gender violence, among other acts that violate and deprive them of their fundamental rights. A social and legal analysis of the legal framework given to these issues is therefore carried out and, for practical reasons, we will only focus on certain legal systems. It is our understanding that, for reasons which we shall explain below, the examples given are the most relevant, either because they are referring to States that do not yet fully recognize that every human being has the right to a free existence - including the right to be free from persecution and violence - or, on the contrary, by the way in which certain States has contributed - with regard to the foundations and assumptions of the granting of the refugee’s status to women who are subjected to gender violence- with significant changes in the interpretation of the Convention relating to the Status of Refugees.